2008
DOI: 10.1073/pnas.0803862105
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Tic20 is essential for apicoplast protein import

Abstract: Apicomplexan parasites harbor a secondary plastid that has lost the ability to photosynthesize yet is essential for the parasite to multiply and cause disease. Bioinformatic analyses predict that 5-10% of all proteins encoded in the parasite genome function within this organelle. However, the mechanisms and molecules that mediate import of such large numbers of cargo proteins across the four membranes surrounding the plastid remain elusive. In this work, we identify a highly diverged member of the Tic20 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
270
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(281 citation statements)
references
References 27 publications
6
270
0
1
Order By: Relevance
“…Here, the 11-stranded β-barrel of GFP was split into saGFP1-10, comprising β-strands 1-10 (short 1-10), and a saGFP11 (short 11) fragment, containing β-strand 11. Neither fragment was fluorescent by itself, but when located in the same cellular subcompartment, the two fragments assembled into fluorescent GFP (35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the 11-stranded β-barrel of GFP was split into saGFP1-10, comprising β-strands 1-10 (short 1-10), and a saGFP11 (short 11) fragment, containing β-strand 11. Neither fragment was fluorescent by itself, but when located in the same cellular subcompartment, the two fragments assembled into fluorescent GFP (35).…”
mentioning
confidence: 99%
“…Because of the paucity of data concerning the topology of chloroplast Omp85 proteins and the importance of the POTRA domain as a central functional element in the models of chloroplast OMP integration/assembly and preprotein import, we decided to investigate the topology of the atToc75-III (AT3G46740) and atToc75-V (AT5G19620). We applied the recently established self-assembling split GFP (saGFP) (34), which has been used to determine membrane protein topology in vivo before (35). Here, the 11-stranded β-barrel of GFP was split into saGFP1-10, comprising β-strands 1-10 (short 1-10), and a saGFP11 (short 11) fragment, containing β-strand 11.…”
mentioning
confidence: 99%
“…Once delivered to the apicoplast, proteins have to cross three additional membranes. Recently, we demonstrated that a homolog of Tic20, a component of the translocon of the inner chloroplast membrane (Tic) 4 complex in plants, is likely required for protein import across the innermost membrane of the apicoplast (12). To date bioinformatics searches have failed to identify a matching translocon of the outer chloroplast membrane in apicomplexans (13).…”
mentioning
confidence: 99%
“…Stromal proteins are transported across membranes three and four, presumably mediated by a Toc/Tic (translocon of the outer/inner chloroplast membrane)-like system as it is known from primary plastids. Core components like a Toc75 homolog and several Tic factors were identified by in silico analyses and partially characterized in diatoms and related organisms (17)(18)(19).…”
mentioning
confidence: 99%